The Public Health Intervention for International Students at Universiti Malaysia Sabah, Malaysia - Hazeqa Salleh; Pang, Nicholas Tze Ping; Mohammad Saffree Jeffree; Helen Benedict Lasimbang; Syed Sharizman Syed Abdul Rahim; Azizan Omar; Mohd Amiruddin Mohd Kassim; Farhana Harzila Mohd Bahar; Syaza Putri Zainudin; Assikin Muhamad (Penerbit UMS, 2021)
Background: COVID-19 pandemic that started in Wuhan, Hubei Province, China, has spread globally, and Sabah is one of the states in Malaysia that is affected by it. The outburst in social media on discrimination against the people from China impacted the international students from China. Thus, University Malaysia Sabah (UMS) had to play a role in mitigating the COVID-19 pandemic and protecting its students. This article aimed to describe the actions taken by UMS for its international student from China during the early phase of the COVID-19 pandemic. Methods: This study used a cross-sectional design where all 379 students from China in UMS were screened from February 2020 until March 2020 during the early phase of COVID 19. Results: During this study period, 0.5% of the students were classified as Persons under Investigation (PUI), while 99.5% were classified as Person under Surveillance (PUS). Conclusion: The public health interventions included surveillance, contact tracing, monitoring, quarantine, isolation, social distancing, mental health support, and mental health intervention activities. These actions to control the pandemic reduce the state health department's health burden and help the students in need.